Pricing strategies for blockchain payment service under customer heterogeneity - Li, Yuze; Jiang, Shangrong; Shi, Jianming; Wei, Yunjie (International Journal of Production Economics, 2021)
The growing popularity of cryptocurrency payment among supply chain members have resulted in considerable waiting in blockchain payment services. In response, service providers offer “priority payment” which allows users to pay additional transaction fee in exchange for priority transaction processing. Despite its growing popularity, there is very limited formal research that studies this service and its impact. In this paper, we examine the impact of the priority option on SC members' blockchain payment service adoption behavior, payment service provider's strategies, as well as his revenue generation. We find that offering priority blockchain payment option increases heavy members' usage of the option and reduces their usage of the waiting blockchain payment option. On the other hand, it boosts certain light players' usage of both blockchain payment services when the transaction fee rate is not too high. The service provider should charge a lower (higher) transaction fee rate if the trust-enabling rate of the priority blockchain payment option is relatively high (low). Finally, we demonstrate that offering priority blockchain payment option actually reduces his revenue when the trust-enabling rate of the option is sufficiently low. Thus, blindly charging transaction fees actually does more harm than good to the service providers.